DISIPLIN PASAR PERBANKAN DI INDONESIA Pengujian Empiris Pada Bank Umum Konvensional dan Syariah - , Hasan, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A sound banking system is vital in supporting a sound and strong economy. One of the important pillars of a sound banking system is market discipline. Market discipline is the reaction of the market makers on the risks taken by banks as a form of supervision and discipline. Various phenomena in the monetary crisis of 1998 and the global crisis in 2008 showed that there were symptoms of market discipline. However, research on Indonesian market discipline is still rare. Besides testing the existence of market discipline by depositors in the deposit insurance era by the Indonesia Deposit Insurance Corporation (LPS), this study also aims to examine differences in market discipline by depositors before and after the policy of increasing the value of deposits covered by a Rp2billion. This study also intends to examine the differences between market discipline by depositors of Islamic banks with conventional banks. The data used are annual data from the Indonesian Banking Directory (DPI) for market discipline 2005-2009 observation period. By using data from 120 banks, the total obtained observations are 600. The dependent variable is the change in deposits, which is used as proxy for market discipline in t period. The independent variables used are CAR, APB, NIM, and LDR as proxy of financial risk / fundamental condition of the bank in t-1 period. The test results with fixed-effects model indicates the existence of market discipline in Indonesia, with negative reaction by depositors on the APB, positive reaction by depositors on the NIM, and positive reaction by depositors to the LDR. This research also shows that market discipline is stronger detected in the period 2005-2007 than the period 2008-2009. This study also indicate that market discipline by depositors of Islamic banks are stronger than conventional ones. Limitations, suggestions, implications and contributions of this research are discussed further in the concluding section.